The Financial Depth of Emerging Markets: The Case of Russia. (May 2013) - Mirkin, Yakov; Kuznetsova, Olga; Kuznetsov, Andrei
The purpose of this article is to assess the financial depth of the Russian economy in the context of its main rivalries within the BRIC group. The Russian financial market is evaluated by a set of key indicators that characterize the level of maturity of the national financial system in respect to international standards. This task is implemented through descriptive analysis of extensive international data generated from a time series covering the period 1995–2010. The article demonstrates that, in comparison to other emerging markets, and its closest competitors Brazil, India and China, the financial depth of the Russian economy may be characterized as inadequate. In the Russian financial market potential for growth is combined with exceptionally high risks. Insufficient depth of the financial system undermines its long-term competitiveness and exacerbates its exposure to shocks in the international market.